PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Purba, Imelda R.; Mahendra, A. (UNIKA Santo Thomas, 2023)
The purpose of this study is to obtain empirical evidence that there is an influence between the variables of profitability, liquidity, and leverage on bond ratings in property and real estate companies in the 2019-2021 period.. This type of research is quantitative research. The data used in this study is secondary data. The population in this study includes all property and real estate companies listed on the IDX in the 2019-2021 period. The sample in this study were 10 companies that met the criteria. The sampling technique in this study used purposive sampling. The data analysis used to test the hypothesis is logistic regression with a significance level of 5% and by using the SPSS version 25 tool. The results of this study indicate that the variables of profitability, liquidity, and leverage partially and simultaneously affect bond ratings.